PHYSICAL ACTIVITY INDEX IN PHYSICAL EDUCATION COURSE OF STUDENTS (Fiep Bulletin - online, 2016)
Kasari, D., University of Montana, 1976 with questions about intensity: In order to analyze the level of physical activity in students of physical education at a private university, the questionnaire Level Physics, SOURCE fitness was applied physical activity. This study was conducted with 121 students in higher education. What was observed in this group of students of physical education is that men are more physically active, but related to the course we have few physical assets, there is a large percentage of students who fit as sedentary. What is worrying, after all are students of physical education, which encourage women to practice physical activity, but they themselves do not practice. But those numbers may improve from students to practice any physical activity and have a balanced diet. Consequently can improve the quality of life and become healthier professionals.
Keywords: Quality of life; academic; intensity